(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This research aims to determine the analysis of the need for teaching materials for Arabic writing skills with a conservation perspective and methods. In researching the development of teaching materials with a learning perspective for Arabic writing skills with a conservation perspective, namely analyzing the need for developing new products (models, methods, media, teaching materials) and analyzing the feasibility and conditions for development product. The development of a product can be initiated by a problem in an existing/applied product. Problems can arise and occur because existing or available products are no longer relevant to target needs, learning environment, technology, student characteristics and so on. After analyzing the problem of the need for new product development, we also need to analyze the feasibility and requirements of product development. The analysis process can be carried out by asking several questions. Analysis of new products needs to be carried out to determine the feasibility if the product is implemented, in particular the development of teaching materials for Arabic writing skills with a conservation perspective. The results of this research reflect a good understanding of the concept of environmental sustainability. illustrates a consistent effort to relate environmental issues in an Arabic language context. I feel that the conservation elements in Arabic are applied effectively in this paper. Appropriate Use of Arabic: The use of Arabic in this paper feels natural and fluent, Terminology related to conservation is used correctly and appropriately. that the author avoids significant grammatical or syntactic errors, Cultural and Social Context: The author successfully integrates conservation values that are appropriate to Arab culture. that this article can provide a good understanding to readers with diverse cultural backgrounds. Suitability of the purpose of the article: the purpose of the article to educate about conservation in Arabic is achieved well. The environmental issues raised in this article are relevant and significant for Arab audiences. Conclusion Based on the rating scale above, provides an assessment [score] of the validity of this paper in combining Arabic with conservation insights.